Effect of liraglutide on the dysglycemia, inflammation, and gut microbiota in prediabetic KKay mice - Zhang, Ying; Yang, Xiaoxiao; Yang, Ping; Sun, Huihuan; Chen, Lijuan; Zhang, Xiaojun; Liu, Shudong (Frontiers in Pharmacology, 2025)
Prediabetes is a significant risk factor for type 2 diabetes mellitus (T2DM). Emerging evidence suggests that glucagon-like peptide-1 receptor agonists (GLP-1RAs) may modulate the gut microbiota and improve dysglycemia in T2DM. In this study, we investigated the effects of liraglutide on dysglycemia and gut microbiota in prediabetic mice. KKay mice were fed a high-fat diet to establish prediabetes. The prediabetic mice were then treated with a daily intraperitoneal injection of liraglutide for 12 weeks. 16S rDNA sequencing was employed to investigate alterations in the gut microbiota in prediabetic mice and liraglutide-treated prediabetic mice. The gut bacterial metabolites in the ileal contents of prediabetic mice were measured via a liquid chromatography‒mass spectrometry (LC‒MS) system. Prediabetic mice presented significantly increased body weights, blood glucose levels, and inflammatory factor levels and decreased GLP-1 levels. Liraglutide treatment improved dysglycemia and insulin secretion and inhibited systematic and tissue inflammation in prediabetic mice. Prediabetic mice presented pronounced increases in the abundance of f_Ruminococcaceae, g_Anaerotruncus, s_Anaerotruncus_sp_G3_2012, s_Ligilactobacillus_murinus, s_Desulfovibrio_fairfieldensis, g_Ligilactobacillus, g_Parabacteroides, g_Butyricimonas, and g_unclassified_Ruminococcaceae. Liraglutide treatment changed the intestinal microbiota composition and related signaling pathways. Our preliminary results demonstrate that GLP-1RA liraglutide exerts beneficial effects by improving dysglycemia and body weight, inhibiting inflammation, and modulating gut microbiota in prediabetic mice, potentially contributing to delaying or preventing the progression from prediabetes to overt diabetes.